Original article (Folia Neuropathologica, 2011)

(untitled) - Lewandowska, Eliza; Dziewulska, Dorota; Parys, Magdalena; Pasennik, Elżbieta
Granular osmiophilic material (GOM) is a pathognomonic feature of CADASIL that may be a consequence of pathological processes triggered by Notch3 mutations. Since knowledge of the effects of CADASIL-associated GOM deposits is important to understand the molecular pathogenesis of this disorder, we performed a thorough ultrastructural analysis of GOM morphology in the skin and muscle arterioles in CADASIL patients. Electron microscopy revealed numerous GOM deposits with different morphology including size, shape and osmiophilic density. Osmiophilic granular material of high density was frequently observed in part of GOM deposits located near vascular smooth muscle cells (VSMC) while a part localized distally from the cell body was less dense and loose. On the basis of our observations we postulate that GOM can be formed on the surface of VSMC in the arteriolar wall and penetrate from these cells into the basement membrane and/or extracellular matrix. The dispersion of granules, which form GOM deposits, may be one of the factors triggering the thickening and changes in the basement membrane and/or extracellular matrix.